Ex Vivo Human Trabecular Bone Model for Biocompatibility Evaluation of Calcium Phosphate Composites Modified with Spray Dried Biodegradable Microspheres. Issue 10 (9th April 2013) - Schnieders, Julia; Gbureck, Uwe; Germershaus, Oliver; Kratz, Marita; Jones, David B.; Kissel, Thomas
Abstract Our aim was to study the suitability of the ex‐vivo human trabecular bone bioreactor ZetOS to test the biocompatibility of calcium phosphate bone cement composites modified with spray dried, drug loaded microspheres. We hypothesized, that this bone bioreactor could be a promising alternative to in vivo assessment of biocompatibility in living human bone over a defined time period. Composites consisting of tetracycline loaded poly(lactic‐co‐glycolic acid) microspheres and calcium phosphate bone cement, were inserted into in vitro cultured human femora head trabecular bone and incubated over 30 days at 37°C in the incubation system. Different biocompatibility parameters, such as lactate dehydrogenase activity, alkaline phosphatase release and the expression of relevant cytokines, IL‐1β, IL‐6, and TNF‐α, were measured in the incubation medium. No significant differences in alkaline phosphatase, osteocalcin, and lactate dehydrogenase activity were measured compared to control samples. Tetracycline was released from the microspheres, delivered and incorporated into newly formed bone. In this study we demonstrated that ex vivo biocompatibility testing using human trabecular bone in a bioreactor is a potential alternative to animal experiments since bone metabolism is still maintained in a physiological environment ex vivo.